Effective Management of Employee Performance : Case Study Of a Malaysian ICT Company - Ng, Kok Kheing (2014)
Globalisation and current economic climate has created pressure on companies to look into all facets of its strategy in order to establish and maintain its competitive advantage. Human capital is being recognised as central in such an endeavour and a key contributor to an organisation’s success. Therefore, it is imperative that the performance of employees is managed effectively in such a manner that enables high levels of productivity and performance. However, organisations at large face the challenges of getting the best out of their Performance Management practices. This paper presents a Performance Management practices case study on ICT Co, a Malaysian Small Medium Enterprise (SME) in the Information and Communication Technology (ICT) industry. Its objective were threefold: (1) Identifying Key Success Factors (KSF) that contributes to effective Performance Management practices by expanding on the findings of Fortune’s Most Admired Companies (FMACs) by Houldsworth and Jirasinghe (2006); (2) Evaluating the effectiveness of the current Performance Management practices of ICT Co as perceived by its employees; and (3) To identify gaps and provide the necessary recommendations within the context of the organisation and the environment it operates in. Four Key Success Factors (Performance Metrics, Managerial Capability, Performance Management Process and Performance Rewards) were identified and literature review were utilised to discover main characteristics associated with effectiveness of each factor. This study was planned with a triangulation research methodology in mind. Primary data used for analysis were collected using quantitative questionnaire, where a total of 75 respondents participated in the survey. Statistical data analyses were then carried out on the collected data and discussions of its results were enhanced using the input from data collected using the qualitative semi-structured interview of 7 Line Managers in ICT Co. The respondents for both methods were thought to provide good representation of the company as the questionnaire respondents made up 91.4% of the employee population while the Line Managers were selected equally from all the departments within the company. Respondents were found to generally lean towards agreement that there is presence of the required KSF with Performance Rewards being observed as the factor with the lowest presence. Analysis showed that all four KSFs had positive correlation with effective Performance Management practices. Managerial Capability showed the strongest relationship and Performance Metrics the weakest. Practical recommendations were then proposed to increase the presence and correlation of each KSF. The three key academic contribution from this study were: (1) There is a need to tweak the Balance Scorecard mechanism to fit into an SME’s context; (2) National culture needs to be considered as an influencing factor when designing Performance Management practices; and (3) The perceived strength of non-financial rewards was not strong in the researched context but it could be used as a complementing motivation mechanism. In terms of managerial implications, the three key highlights were: (1) Hiring of the right talent could contribute to creating and maintaining the right performance culture, and hence should be given due attention; (2) Aligning departmental performance planning process with the business planning cycle is important; and (3) Line Managers needs to be equipped with people management skills to aid them in managing employee performance. In conclusion, there are key factors and characteristics that could influence the effectiveness of Performance Management practice which organisations would need to be aware of and focus on.